P. falciparum: Merezoite Surface Protein-8 peptides bind specifically to human erythrocytes. (2003)
This work determined Plasmodium falciparum merozoite surface protein-8 (MSP-8) regions specifically binding to membrane surface receptors on human erythrocytes. Five high activity binding peptides (HABPs), whose binding to erythrocytes became saturable and sensitive on being treated with neuraminidase and chymotrypsin were identified from the MSP-8 protein. Those amino acids directly involved in interaction with erythrocytes were also determined for each one of the HABPs. Some of them specifically recognized 28, 46, and 73 kDa erythrocyte membrane proteins. Some HABPs inhibited in vitro P. falciparum merozoite invasion of erythrocytes by up to 98%, suggesting the MSP-8 protein’s possible role in the invasion process.